Oscillation criteria for nonlinear neutral hyperbolic equations with functional arguments - Shoukaku, Y.; Stavroulakis, I.P.; Yoshida, N. (Нелінійні коливання, 2011)
This paper is devoted to the study of oscillatory behavior of solutions to nonlinear neutral hyperbolic equations with functional arguments by using the integral averaging method and generalized Riccati techniques. First, we establish oscillation results for nonlinear neutral hyperbolic equations by reducing the multi-dimensional oscillation problems to one-dimensional oscillation problems for functional differential inequalities. Secondly, we present oscillation results for nonlinear neutral hyperbolic equations by utilizing Riccati techniques. Вивчається коливна поведiнка розв’язкiв нелiнiйних гiперболiчних рiвнянь нейтрального типу з функцiональними аргументами з допомогою методу iнтегрального усереднення та узагальненої технiки Рiккатi. По-перше, отримано результати про коливання для нелiнiйних гiперболiчних рiвнянь нейтрального типу шляхом зведення багатовимiрних задач про коливання до одновимiрних задач про коливання для функцiонально-диференцiальних нерiвностей. По-друге, отримано результати про коливання для нелiнiйних гiперболiчних рiвнянь нейтрального типу з використанням технiки Рiккатi.